A linearization-based theory of summative agreement in peripheral-node raising constructions - Yatabe, Shûichi (Proceedings of the 9th International Conference on Head-Driven Phrase Structure Grammar, 2003)
The aim of this paper is to present a theory that explicitly characterizes patterns of summative agreement. The proposed theory builds on my own theory of PNR, presented in Yatabe 2001, and is based on the view that agreement results from a non-lexical constraint that regulates under what circumstances a domain object can be merged with other domain objects by the compaction operation.